RENTABILITAS & LIKUIDITAS TERHADAP STRUKTUR MODAL PADA BANK BUMN SYARIAH DI INDONESIA - ., Fadilla; Putri, Weny (Catholic University Musi Charitas, 2020)
This study aims to find out what influences the capital structure in the 3 (three) largest Sharia Banks in Indonesia, namely Bank Syariah Mandiri (BSM), Bank Negara Indonesia Syariah, Bank of the Republic of Indonesia Sharia (BRIS). This study examines the effect of Return on Assets (ROA), Return on Equity (ROE) and Financing Deposite Ratio (FDR) on KPMM. The data used in this study is secondary data obtained from the quarterly financial statements of the Islamic Bank for 7 years, namely from 2013-2017. The analysis technique used in this study is Multiple Linear Regression. The results of this study prove that Return on Assets (ROA), Return on Equity (ROE) and Financing Deposite Ratio (FDR) affect KPMM together. While partially Return on Assets (ROA) and Return on Equity (ROE) affect KPMM, but FDR has no effect on KPMM